Loki zupa (Luooukezupa) decoction reduced airway inflammation in an OVA-induced asthma mouse model. Issue 1 (December 2016) - Wei, Ying; Abduwaki, Muhammadjan; Li, Mihui; Luo, Qingli; Sun, Jing; Lv, Yubao; Nurahmat, Mammat; Dong, Jingcheng
Abstract Background Loki zupa (Luooukezupa ) decoction, consisting of the roots ofHyssopuscuspidatus Boriss (Shenxiangcao ) andIrishalophila Pall root (Yuanweigen ), is commonly used in Uygur medicine to treat asthma. However, the mode of action of this material has yet to be elucidated. This study aims to investigate the effects ofLoki zupa decoction on the airway inflammation of an ovalbumin (OVA)-induced asthma mouse model. Methods Mice were divided into normal control (NC), asthma (A), high, medium and low doses ofLoki zupa decoction (L 14.0, L 7.0, L 3.5), water extract (LW), n -butanol extract (LN), ethyl acetate extract (LE) and dexamethasone (DEX) groups. Antiasthmatic model was induced by OVA sensitization and challenged using BALB/c mice. Airway hyperresponsiveness (AHR) toward methacholine (Mch) was assessed using Buxco equipment. Lung inflammation was measured by hematoxylin and eosin staining and bronchoalveolar lavage fluid (BALF) cell count and classification. Inflammatory cytokines in BALF and serum were analyzed by Bio-Plex assay, and mRNA levels were investigated by qPCR analysis. The roots ofH. Boriss (250 g) andI. Pall (250 g) were decocted, concentrated and diluted to 14.0, 7.0 and 3.5 g crude herb/kg body weight. The LW, LN and LE of theLoki zupa decoction were prepared and diluted to a dose equivalent to 7 g of crude herb/kg body weight. Results Loki zupa decoction and its extracts significantly attenuated the AHR towards Mch (allP < 0.05). Treatment withLoki zupa decoction and its extracts relieved the infiltration of inflammatory cells in and around the airways, and reduced the total white blood cell (allP < 0.05), neutrophil (allP < 0.05), monocyte (allP < 0.05) and eosinophil (allP < 0.05) counts in the BALF. The BALF samples collected from the mice treated with theLoki zupa decoction and its extracts had lower levels of IL-1β (allP < 0.05), TNF-α (allP < 0.05), IL-2 (allP < 0.05), IL-4 (P = 0.047) and IL-5 (allP < 0.05). The serum samples of these mice also had lower IL-1β (allP < 0.05), TNF-α (allP < 0.05), IL-4 (allP < 0.05) and IL-5 (allP < 0.05) levels and higher levels of IFN-γ (P < 0.001) compared with the OVA-induced asthma mouse model. qPCR analysis revealed thatLoki zupa decoction and its extracts inhibited mRNA expression of IL-4 (allP < 0.05), IL-5 (allP < 0.05) and IL-13 (allP < 0.05) and promoted mRNA expression of IFN-γ (allP < 0.05) in asthmatic mice. Conclusion Loki zupa decoction reduced AHR, attenuated airway inflammation, promoted Th1 and suppressed Th2 cell functions in an OVA-induced asthma mouse model.